Clinical perspectives on the optimal use of lenalidomide plus bortezomib and dexamethasone for the treatment of newly diagnosed multiple myeloma - Paul G. Richardson; Brian G. Durie; Laura Rosiñol; Maria-Victoria Mateos; Angela Dispenzieri; Philippe Moreau; Shaji Kumar; Noopur Raje; Nikhil Munshi; Jacob P. Laubach; Peter O’Gorman; Elizabeth O’Donnell; et al. (Haematologica, 2023)
To improve the outcomes of patients with the otherwise incurable hematologic malignancy of multiple myeloma (MM), a key paradigm includes initial treatment to establish disease control rapidly followed by maintenance therapy to ensure durability of response with manageable toxicity. However, patients’ prognosis worsens after relapse, and the disease burden and drug toxicities are generally more challenging with subsequent lines of therapy. It is therefore particularly important that patients with newly diagnosed multiple myeloma (NDMM) receive optimal frontline therapy. The combination of lenalidomide, bortezomib, and dexamethasone (RVd) has consistently demonstrated a tolerable safety profile with significant and clinically relevant benefit, including deep and durable responses with improved survival in patients with NDMM regardless of their transplant eligibility. Furthermore, comparative studies evaluating this triplet regimen against both doublet and other triplet regimens have established RVd as a standard of care in this setting based upon its remarkable and concordant efficacy. Given the breadth of clinical data, physician familiarity, inclusion in treatment guidelines, and the emerging potential of RVd-containing quadruplet regimens, RVd will likely continue as a key cornerstone of the treatment of NDMM, and its role will therefore likely continue to grow as a therapeutic backbone in the initial treatment of MM.